2016
DOI: 10.1371/journal.pone.0165233
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Two Types of Rabbit Antithymocyte Globulin Induction Therapy in Immunological High-Risk Kidney Recipients: A Prospective Randomized Control Study

Abstract: BackgroundInduction treatment with rabbit polyclonal antithymocyte globulins (ATGs) is frequent used in kidney transplant recipients with donorspecific HLA antibodies and shows acceptable outcomes. The two commonly used ATGs, Thymoglobulin and ATG-F have slightly different antigen profile and antibody concentrations. The two compounds have never been directly compared in a prospective trial in immunological high-risk recipients. Therefore we performed a prospective randomized controlled study comparing the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 30 publications
(31 reference statements)
1
21
0
Order By: Relevance
“…A lower incidence of acute rejection after the induction treatment of THG is mainly attributed to initial lower lymphocyte counts and later recovery of lymphocyte counts in comparison with ATG-F (47,48). By contrast, the only small-size investigation of THG and ATG-F in kidney transplantation showed similar rates of BPAR and T-cellmediated acute rejection in the 2 year follow-up; peripheral Tcell and B-cell counts at 6 and 12 months were similar and sustained in both groups (16). Our analysis revealed comparable results between THG and ATG-F with regard to acute rejection, although SUCRA values indicated that THG might be more efficacious.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…A lower incidence of acute rejection after the induction treatment of THG is mainly attributed to initial lower lymphocyte counts and later recovery of lymphocyte counts in comparison with ATG-F (47,48). By contrast, the only small-size investigation of THG and ATG-F in kidney transplantation showed similar rates of BPAR and T-cellmediated acute rejection in the 2 year follow-up; peripheral Tcell and B-cell counts at 6 and 12 months were similar and sustained in both groups (16). Our analysis revealed comparable results between THG and ATG-F with regard to acute rejection, although SUCRA values indicated that THG might be more efficacious.…”
Section: Discussionmentioning
confidence: 89%
“…Second, we conducted a subgroup analysis of studies involving patients of high or low immunological risk to better reflect real-world scenarios. High immunological risk patients refers to those who have higher risk of developing AR and graft loss after transplantation, including patients with PRA > 20%, or re-transplant, or those who are Africa-American (15,16). Third, we conducted the subgroup analysis by excluding the sensitive studies displayed in the funnel plots.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was also no significant difference in the frequency of nonfatal infectious complications, including CMV infection, between the two ATG formulations, which is consistent with previous observations. 14,15 In contrast, Ducloux et al reported a higher incidence of CMV infections and deaths in the Thymoglobulin group; however, the study used much higher cumulative doses of both agents. 16 Indeed, the benefits of induction therapy with ATGs must be weighed against post-transplant complications, including life-threatening infections.…”
Section: Discussionmentioning
confidence: 89%
“…Early reports [11][12][13] yielded conflicting results on the frequency of acute rejection episodes and treatment safety issues. The literature after 2000 includes only two small studies (a retrospective analysis with a follow-up period of 3 months 14 and a prospective randomized control study with DSA-positive recipients only 15 ), one retrospective study in 255 kidney transplants from donation after cardiac death, with a short ATG low-dose induction protocol 1 ; and the study by Ducloux et al 16 , which reported a greater incidence of CMV disease, malignancy, and death among patients treated with Thymoglobulin induction. Importantly, this large cohort was treated predominantly with cyclosporine A and azathioprine, and the ATGfixed cumulative doses were relatively high, that is, 21 mg/kg in the ATG-Fresenius and 13 mg/kg in the Thymoglobulin group.…”
Section: Introductionmentioning
confidence: 99%